2021
DOI: 10.2147/ijgm.s326929
|View full text |Cite
|
Sign up to set email alerts
|

Enteric-Coated Aspirin and the Risk of Gastrointestinal Side Effects: A Systematic Review

Abstract: Introduction: Aspirin appeared as a medicine to deal with aches and inflammation, but due to its antiplatelet properties, it has evolved into a drug mainly used to avert cardiovascular disease. Regardless of its therapeutic uses, the limiting aspect for aspirin use has been its affiliation with gastrointestinal (GI) toxicity, classifying from acute mucosal damage to GI problems and death. Objective: The aim of this systematic review is to address the question regarding the ECA effect on the gastric mucosa. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…The use of proton pump inhibitors (PPIs), histamine H2receptor antagonists, or enteric-coated aspirin formulations is associated with a higher risk for NSAID-induced enteropathy [130,131]. Indeed, a prospective SBCE study found that PPI use (OR 2.04, 95 %CI 1.05-3.97) and use of enteric-coated aspirin (OR 4.05, 95 %CI 1.49-11.0) were the two most important risk factors for the presence of mucosal breaks [132].…”
Section: Recommendationmentioning
confidence: 99%
“…The use of proton pump inhibitors (PPIs), histamine H2receptor antagonists, or enteric-coated aspirin formulations is associated with a higher risk for NSAID-induced enteropathy [130,131]. Indeed, a prospective SBCE study found that PPI use (OR 2.04, 95 %CI 1.05-3.97) and use of enteric-coated aspirin (OR 4.05, 95 %CI 1.49-11.0) were the two most important risk factors for the presence of mucosal breaks [132].…”
Section: Recommendationmentioning
confidence: 99%
“…Более того, в ходе выполнения метаанализа 6 РКИ, включавших 15 621 участников, были получены данные о том, что в большинстве исследований прием КР-АСК не оказывал защитного влияния на ЖКТ [26].…”
Section: безопасность приема аск в зависимости от лекарственной формы...unclassified
“…Также было установлено, что сопутствующее применение ингибитора протонного насоса омепразола позволяло 2022;12(1):8-18 | СПЕЦИАЛИЗИРОВАННЫЙ МЕДИЦИНСКИЙ ЖУРНАЛ | АТЕРОТРОМБОЗ существенно уменьшить частоту повреждения слизистой желудка по сравнению с изолированным приемом КР-АСК. Результаты метаанализа также свидетельствовали о том, что даже кратковременный прием КР-АСК приводит к отчетливому повреждению слизистой тонкого кишечника [26].…”
Section: безопасность приема аск в зависимости от лекарственной формы...unclassified
“…In an effort to reduce GI injury, a delayed release formulation enteric-coated aspirin (EC-ASA) was developed and is currently widely used for secondary cardiovascular event prevention, usually at doses of 75-100 mg daily. However, whether EC-ASA reduces GI toxicity remains debated [12,13]. Further, EC-ASA is associated with considerable variability in aspirin absorption and resultant antiplatelet effect [14][15][16].…”
Section: Introductionmentioning
confidence: 99%